2015
DOI: 10.2460/javma.246.12.1358
|View full text |Cite
|
Sign up to set email alerts
|

Bovine viral diarrhea virus outbreak in a beef cow herd in South Dakota

Abstract: Introduction of BVDV into a naïve cow herd resulted in a loss of 44% of the calf crop subsequent to reproductive loss, poor thrift, and mucosal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
(18 reference statements)
0
8
0
1
Order By: Relevance
“…Because the period in which BVDV can be detected is comparatively short in TI animals, it is probable that most of the BVDV-positive sera in the present study were from PI bovine [10,24]. In this regard, studies have reported that 63% to 92% of the positive cattle were confirmed as PI [28,29], and 90% of the BVDVpositive pools contained at least one PI animal [26]. As expected, in the current study, the detection of BVDV was higher in younger cattle.…”
Section: Discussionmentioning
confidence: 61%
“…Because the period in which BVDV can be detected is comparatively short in TI animals, it is probable that most of the BVDV-positive sera in the present study were from PI bovine [10,24]. In this regard, studies have reported that 63% to 92% of the positive cattle were confirmed as PI [28,29], and 90% of the BVDVpositive pools contained at least one PI animal [26]. As expected, in the current study, the detection of BVDV was higher in younger cattle.…”
Section: Discussionmentioning
confidence: 61%
“…To our knowledge, this paper represents the first study to examine the impacts of BVDV type 2 persistent infection relevant to dairy cattle production and reproduction in a large dairy herd. Previously, Kane et al (2015) reported information about clinical presentation in PI caused by a single strain of BVDV2, however it was in a Angus and Angus-cross beef herd.…”
Section: Discussionmentioning
confidence: 99%
“…However, challenge with BVDV under experimental conditions often does not reproduce the full variety of manifestations of the disease seen in the field. Specifically, there is a lack of authoritative information about the typical clinical findings throughout the lifespan of PI cattle [11]. This is, in part, due to the short lifespan of PI cattle, which is often less than one year [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otra parte, los animales en los establos con mayor prevalencia de BVD y l o s establos que utilizan IA tienen un menor riesgo de asistencia al parto. Este resultado era esperado, en otros estudios se ha reportado que el peso al nacimiento de becerros positivos a antígenos de BVD son 7 kg más ligeros que su contraparte de becerros negativos (34) . Referente al impacto de la IA sobre la ocurrencia de asistencia al parto, actualmente existen en el mercado una gran variedad de sementales con diferentes características de conformación, incluyendo la facilidad de parto (35,36) .…”
Section: Discussionunclassified